Empowering Women: Understanding Divorce, Equality, and Competition between Genders - Hassan, Ishraq (Integrated Journal for Research in Arts and Humanities, 2023)
Women’s empowerment and gender equality have come a long way over the last century. Today, many societies pride themselves on having made considerable strides towards egalitarianism. However, even the most egalitarian societies admit that gaps still exist. Developing countries are also on course to achieving gender equality. A case study of Bangladesh presented in this research reckons that Bangladesh is a global example. This research aimed to establish the feminist perspective on issues of gender equality and empowerment, divorce, and gender competition. To achieve these objectives, the selected methodology comprised two case studies, one for Bangladesh and another for the UK, which served the purpose of making comparisons. The findings indicate that Bangladesh has made significant progress but lags behind many egalitarian Western societies. Bangladesh’s efforts to achieve equality and empowerment have also caused divorce rates to rise, unlike in the UK. Lastly, gender competition fails to explain the remaining gender gaps.